Coexistence of Anti-GAD and Anti-GABAAR Antibodies in an Autoimmune Encephalitis Patient: A Case Report - Lu X; Wu H; Tan Y; Mao X (International Medical Case Reports Journal)
Xiaoyan Lu,* Hangfei Wu,* Yuhao Tan, Xiaowei Mao Department of Neurology, Changhai Hospital, Naval Medical University (Second Military Medical University), Shanghai, People’s Republic of China*These authors contributed equally to this workCorrespondence: Xiaowei Mao, Department of Neurology, Changhai Hospital, Naval Medical University (Second Military Medical University), Shanghai, People’s Republic of China, Email xiaoweimaoamtf@163.comBackground: Coexistence of autoimmune encephalitis (AE) with multiple autoantibodies is of particular concern because overlying antibodies may cause variation of clinical manifestations. Coexistence of anti-glutamic acid decarboxylase (GAD) and anti-Gamma-aminobutyric acid-α-receptor (GABAAR) antibodies in AE was rare.Case Presentation: A 44-year-old female patient presented to our hospital due to cognitive decline for 4 years, seizures, slowed speech and depression for 2 months. Based on her clinical manifestations and laboratory assessment results (positive anti-GAD and anti-GABAAR antibodies), she was diagnosed as AE with coexisting anti-GAD and anti-GABAAR antibodies. After treatment with intravenous methylprednisolone (at dose of 1000mg/d, 500mg/d, 250mg/d, 120mg/d, 80mg/d for 3 days respectively) and intravenous immunoglobulin (400 mg/kg/d for 5 days), her symptoms gradually improved with exception for the slowed speech. Oral prednisone acetate was continued after discharge, her symptoms of slowed speech improved at 6-month follow-up.Conclusion: We report a case of AE co-existing with anti-GAD and anti-GABAAR antibodies, which has different characteristics from previous cases. Coexistence of neural auto-antibodies should be considered when patients suspected with autoimmune encephalitis.Keywords: autoimmune encephalitis, anti-GAD antibody, anti-GABAAR antibody